Music therapy for adolescents with psychiatric disorders: An overview - Freitas, Carina; Fernández Company, José Fernando; Pita, Marisela Figueira; García-Rodríguez, María (Clinical child psychology and psychiatry, 2022)
Background Although it is true that adolescence is a stage of evolutionary development in which there are innumerable windows of opportunity, it is also the peak age at which some psychiatric disorders may appear. On the other hand, music is an auditory stimulus that interests and motivates youngsters, as it is used for identity, social connection, and emotional regulation. Methods We conducted a strategic search by consulting scientific databases. The following search terms were employed: Music Therapy AND Psychology AND Psychiatry AND Adolescents. The following international electronic databases were searched: Medline, Ovid, and Cochrane Library. Results A total of 142 sources were identified from which 9 papers on music therapy published exclusively in scientific journals specialized in psychology or child psychiatry were selected. The total number of participants was 651. The studies reported that music therapy interventions have the potential to improve self-esteem, social engagement, decrease social isolation, and depressive and anxiety symptoms in psychiatric adolescents (both in inpatient and outpatient settings). Conclusion Given the heterogeneity and methodological quality of the few studies included, it is complex to extrapolate and generalize results. More quality research is needed to expand music therapy interventions on youth mental health.
Keywords: music therapy; adolescents; psychopathology; psychiatric disorders; systematic review; JCR; Scopus